2001
DOI: 10.1109/41.925591
|View full text |Cite
|
Sign up to set email alerts
|

Perfect tracking control based on multirate feedforward control with generalized sampling periods

Abstract: In this paper, a novel perfect tracking control method based on multirate feedforward control is proposed. The advantages of the proposed method are that: 1) the proposed multirate feedforward controller eliminates the notorious unstable zero problem in designing the discrete-time inverse system; 2) the states of the plant match the desired trajectories at every sampling point of reference input; and 3) the proposed controller is completely independent of the feedback characteristics. Thus, highly robust perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
117
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(118 citation statements)
references
References 17 publications
(32 reference statements)
0
117
0
Order By: Relevance
“…These coefficient matrices and the state variable are as shown in (7) to (10), respectively. A is a n × n regular matrix.…”
Section: E-ptcmentioning
confidence: 99%
See 1 more Smart Citation
“…These coefficient matrices and the state variable are as shown in (7) to (10), respectively. A is a n × n regular matrix.…”
Section: E-ptcmentioning
confidence: 99%
“…The perfect tracking control (PTC) (10)- (12) system is a perfect inverse system composed of a multi-rate system. Multi-rate is a particularly effective technique for systems where the sampling frequency is limited.…”
Section: E-ptcmentioning
confidence: 99%
“…In Case 2, there is one stable zero, Case 3 has one real stable zero and one real unstable zero, and Case 4 is the case having one real unstable zero. In the perfect tracking control method using the conventional multirate feedforward (13) , perfect tracking is possible only in the cases where there was no unstable zero in the continuous time system (Case 1, 2). Whereas, in the proposed method with the extended state variable trajectory generation, it is demonstrated that perfect tracking is possible even in cases having continuous time unstable zeros (Case 3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have proposed the Perfect Tracking Control (PTC) method (13) using multirate feedforward, which is a method of designing a stable inverse system without approximating to the unstable discretization zeros. This method is applied to high-precision stages (14) (15) , HDD (7) , Atomic Force Microscope (AFM) (16) , machine tools (17) , etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation